1996
DOI: 10.1093/oxfordjournals.aje.a008963
|View full text |Cite
|
Sign up to set email alerts
|

Relation of C-Reactive Protein and Coronary Heart Disease in the MRFIT Nested Case-Control Study

Abstract: The authors measured the relation between C-reactive protein, alpha 1 acid glycoprotein and albumin, an acute phase protein, and subsequent risk of myocardial infarction and coronary heart disease death in a nested case-control study among the Multiple Risk Factor Intervention Trial (MRFIT) participants. There were 98 myocardial infarction cases, 148 coronary heart disease deaths, and 491 controls. The cases and controls were followed for up to 17 years for deaths and 6-7 years for myocardial infarction cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
391
2
9

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 954 publications
(418 citation statements)
references
References 0 publications
16
391
2
9
Order By: Relevance
“…We found similar associations for abdominally obese participants with elevated CRP levels showing an increased risk for CHD compared with abdominally obese participants with low CRP levels. Previous studies linking CRP levels to CHD were performed largely in populations with a lower prevalence of obesity than that of the current US population 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32. In the 2 largest published studies of CRP and CHD disease,25, 27 the mean body mass index (in  kg/m 2 ) of participants ranged from 25 to 26, lower than the recently reported mean of 28.7 in US adults,33 indicating the clinical need for data regarding CRP in obese populations.…”
Section: Discussionmentioning
confidence: 99%
“…We found similar associations for abdominally obese participants with elevated CRP levels showing an increased risk for CHD compared with abdominally obese participants with low CRP levels. Previous studies linking CRP levels to CHD were performed largely in populations with a lower prevalence of obesity than that of the current US population 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32. In the 2 largest published studies of CRP and CHD disease,25, 27 the mean body mass index (in  kg/m 2 ) of participants ranged from 25 to 26, lower than the recently reported mean of 28.7 in US adults,33 indicating the clinical need for data regarding CRP in obese populations.…”
Section: Discussionmentioning
confidence: 99%
“…Kuller et al, in a nested case-control study of stored samples of serum from 492 controls and 246 coronary event cases in the Multiple Risk Factor Intervention Trial, found that a raised CRP concentration at entry was a highly significant risk factor, 18 suggesting that CRP measurement may provide important prognostic information even before symptoms appear.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] In more recent years, several nested case-control and cohort studies have also reported that the risk for CVD was related to baseline CRP concentrations. 18,19 This relation was interpreted as a confirmation of the role of CRP itself as a risk factor for coronary disease by inducing mononuclear cells to express tissue factor, the initiator of the extrinsic pathway of coagulation, further stimulating vascular thrombosis. In addition, increased CRP concentrations in atherosclerotic patients usually reflect the inflammatory condition of the vascular wall, which may play an important role of changes in plaque morphology, rupture, and thrombosis.…”
Section: Introductionmentioning
confidence: 94%
“…The differences observed for orosomucoid in serum in our study occur within the reference interval. Likewise, the subclinical increase of inflammatory markers such as Creactive protein, which has been found to be an independent risk marker of mortality in epidemiological studies [18,19], does not allow individual classification based on normal or elevated values. In contrast, the mean occurrence of UOER values 9−12 times higher than the upper reference value readily allows classification of individuals as either normal or abnormal regarding UOER.…”
Section: Discussionmentioning
confidence: 99%